Campus Market Segmentation Through the Binary Logistic Regression and GIS Technology - Nengsih, Titin Agustin; Huda, Imam Arifa’illah Syaiful; Ladin, Urwawuska (Politeknik Harapan Bersama, 2024)
Understanding and targeting specific consumer segments has become paramount in the evolving marketing landscape. Within the confines of a university campus, a unique characteristic of potential consumers with distinct preferences and behaviors exists. The aim of this research is to model of interest in choosing UIN Sulthan Thaha Saifuddin Jambi. This research uses primary data, data from high school students of XII students in Jambi Province. The sample used 1205 students from six districts/cities in Jambi Province. Binary Logistic Regression analysis is employed for the analysis. The findings indicate that the variables of gender, region of origin, and majors of high school students have a significant influence on the interest in choosing UIN Sulthan Thaha Saifuddin Jambi. The regional origin variables, Merangin Regency and East Tanjung Jabung Regency did not have a significant effect on the interest in choosing UIN Sulthan Thaha Saifuddin Jambi. Meanwhile, Jambi City, Kerinci Regency, Tebo Regency, and Bungo Regency influenced the interest in choosing UIN Sulthan Thaha Saifuddin Jambi. The variables from school majoring in science and social studies have a significant influence on the intention to choose UIN Sulthan Thaha Saifuddin Jambi.